2007
DOI: 10.1248/bpb.30.1167
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Amount of Drug Delivered to Lungs and Amount Released from Diskhaler by Inhalation with Tapping

Abstract: It is well known that drug residue remains in a fluticasone propionate Diskhaler (FP-DH) following a single inhalation. Thus, the inspiratory ability of the patient has an influence on the effects of the drug. In a previous study, we reported that the amount of drug remaining in an FP-DH was decreased by tapping the device after the first inhalation. In the present study, we investigated the relationship between the amount of drug delivered to the lungs and amount of drug released from the FP-DH by inhalation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“… 6 A minimal IF of 30 liters/minute is generally recommended to actuate most DPIs, 6 whereas studies show that higher IFs create smaller drug particle sizes for greater deposition of the medication into the lower respiratory tract. 7 , 8 For low to medium high resistance DPIs, a peak IF (PIF) of at least 60 liters/minute is recommended. 9 Two studies have demonstrated greater improvements in lung function with nebulized therapy compared with DPI in patients with a suboptimal PIF.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A minimal IF of 30 liters/minute is generally recommended to actuate most DPIs, 6 whereas studies show that higher IFs create smaller drug particle sizes for greater deposition of the medication into the lower respiratory tract. 7 , 8 For low to medium high resistance DPIs, a peak IF (PIF) of at least 60 liters/minute is recommended. 9 Two studies have demonstrated greater improvements in lung function with nebulized therapy compared with DPI in patients with a suboptimal PIF.…”
Section: Introductionmentioning
confidence: 99%